(untitled) (JISIP (Jurnal Ilmu Sosial dan Pendidikan), 2022)
The speaker on Cokro TV’s Youtube video, Ade Armando, expressed his opinion about the discourse of non-mahram which has invited controversy. The discourse of non-muhrim has sparked debate because it is associated with social problems that occur in society, namely choosing a doctor who is adjusted to the gender of the patient. This research emphasizes more on the ideology that the speaker wants to convey and the strategies used by the speaker to express his ideology. The critical analysis model used in this research is Van Leeuwen’s critical analysis model. This research model is used to determine the social actors supported and marginalized by the speaker. This research uses a qualitative research approach with content analysis method. The results showed that the speakers used exclusion and inclusion strategies. The exclusion strategy used by the speaker leads to a passive discourse strategy, while the inclusion strategy used by the speaker leads to an identification discourse strategy.